If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 13x + 14y = 41 Solving 13x + 14y = 41 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-14y' to each side of the equation. 13x + 14y + -14y = 41 + -14y Combine like terms: 14y + -14y = 0 13x + 0 = 41 + -14y 13x = 41 + -14y Divide each side by '13'. x = 3.153846154 + -1.076923077y Simplifying x = 3.153846154 + -1.076923077y
| 5x+2(x-3)= | | 4(x+8)+3=7x-3(x-5) | | -x^2-5x+12=0 | | 8x-8=8(x+4) | | X^2-3.5x+2.5=0 | | 8x+12=20+4x | | -28+x^2-3x=0 | | x^2+xc+c^2=0 | | 3-2x=21+4x | | 3w+6w=45 | | 2x=14+-4y | | 2x=14+-4 | | ln(x)-ln(x-6)=4 | | 4x+8+9=-15 | | 4x+8+9=15 | | 6x+1.2y=20 | | 4x=3/8 | | 6b+9p=153 | | x-9x=48 | | x-9b=48 | | 6-3(5x^2-3x+5)=0 | | 1x-8+8=13 | | 8x+2=9x-6 | | 45x^2-180x+180+9x-18+5=0 | | 195=(x*0.3)+x | | 4x^2+6x+8=0 | | 78=13m | | 3000=(x*0.3)+x | | x-7+8x=15 | | a(4x+3)-13c(4x-3)+20(4x+3)= | | 7x+14-7x+14-2z^2+8=0 | | 7x+14-7x-14-2z^2+8=0 |